Glyphosate and AMPA have low mobility through different soil profiles of the prosecco wine production area: A monitoring study in north-eastern Italy - Mencaroni, Marta; Cardinali, Alessandra; Costa, Leonardo; Morari, Francesco; Salandin, Paolo; Zanin, Giuseppe; Dal Ferro, Nicola (Frontiers in Environmental Science, 2022)
Contamination of the environment by glyphosate (GLP) and its metabolite aminomethylphosphonic acid (AMPA) is still of major concern worldwide due to specific interactions among these molecules and soil and water. Two monitoring sites were established in the Prosecco wine production area (Conegliano and Valdobbiadene) in northeastern Italy, which has been included in the UNESCO’s World Heritage List since 2019. The study aims to increase the knowledge about GLP dynamics in this area where it has been intensively used by farmers and the potential risk for groundwater pollution is still debated. Each site was equipped with two soil-water monitoring stations consisting of multi-sensor soil probes and suction cups at three soil depths (10, 30 and 70 cm). Soil and water were sampled for 10 and 6 months respectively and analyzed for GLP and AMPA concentrations, for a total of 242 samples to describe their vertical movement and dissipation dynamics. Soil properties, in particular the different forms of Fe and Al oxides contents, and Freundlich adsorption coefficients were quantified along the soil profile. First attempts showed that glyphosate dissipation time was 36±8 days in Conegliano and Valdobbiadene soil and fully completed in both after 6 months. In contrast, AMPA dissipation dynamics -first described by an original equation- was longer than GLP and fully dissipated after almost 300 days. GLP showed a strong binding affinity with clay and Fe and Al chelated to soil organic matter, which likely acted as cation bridges and in turn led to low GLP mobility. GLP and AMPA were mostly detected after heavy rainfall events at 70 cm depth, likely bypassing the porous matrix of the intermediate layers.